Sjögren's syndrome: comparison among the main imaging techniques in the study of major salivary glands - R. Gerli; G. Valesini; A. Iagnocco; C. Contessa; C. Campana; A. Dorigo; P. Zucchetta; M. Andretta; M. Carotti; F. Salaffi; R. Ramonda; P. Frallonardo; et al. (PAGEPress Publications, 2011)
Sjögren's syndrome (SS) is a chronic inflammatory disease with an autoimmune etiology, that affects exocrine glands, in particular salivary and lacrimal glands. Among the diagnostic criteria of SS, imaging tecniques play an important role. The aim of our study is to compare three imaging tecniques, such as sonography, scintigraphy and sialography in the evaluation of major salivary glands. The use of the these tecniques is of great importance for the diagnosis of SS. Sonography is the most frequently used for its prompt execution, non invasivity, great acceptance by the patient and low cost. In the diagnostic patient management of SS, sonography results are eventually confirmed by the other imaging tecniques, sialography and scintigraphy.